Impact of Cybersecurity Regulations on Corporate Compliance Practices in Japan - Yamada, Rina (International Journal of Law and Policy, 2024)
Purpose: The aim of the study was to analyze impact of cybersecurity regulations on corporate compliance practices in Japan. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: In Japan, cybersecurity regulations have significantly influenced corporate compliance practices. The Act on the Prohibition of Unauthorized Computer Access, along with the Penal Code, outlines stringent measures against cybercrimes, mandating corporations to adopt robust cybersecurity protocols to protect against unauthorized access and data breaches. Furthermore, comprehensive data protection laws, such as the Act on the Protection of Personal Information (APPI), require companies to obtain explicit consent for data processing, ensuring a higher standard of data privacy and security compliance. Unique Contribution to Theory, Practice and Policy: Institutional theory, resource dependence theory & contingency theory may be used to anchor future studies on cybersecurity regulations on corporate compliance practices. Organizations should prioritize building a robust cybersecurity governance framework that integrates regulatory compliance requirements into broader risk management strategies. Policymakers and regulators should adopt a risk-based approach to cybersecurity regulation that takes into account the diverse needs and capabilities of organizations across different sectors and geographical regions.